1995
DOI: 10.1007/bf00203736
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modulation of intraepithelial Langerhans' cells and stromal macrophage/dendrocyte populations in human papillomavirus-associated squamous intraepithelial lesions of the cervix

Abstract: Ninety-four cervical biopsies from normal tissue to high-grade squamous intraepithelial lesion (SILs) were examined for the presence of intraepithelial Langerhans' cells and subpopulations of stromal macrophages/dendrocytes by immunohistochemistry using anti-S100, -L1, -CD68 and -factor XIIIa antibodies. Human papillomavirus (HPV) detection was performed in all cases by using first a mixture of DNA probes for 14 HPV types commonly found in anogenital biopsies at low stringency conditions (Tm -40 degrees C) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 72 publications
4
62
0
3
Order By: Relevance
“…Nevertheless, we and others have suggested that other factors may contribute to the sensitivity of the TZ to SIL development. 6,17,18 For example, we have observed that the density of LC is significantly reduced and the immunosuppressive cytokine IL10 is more frequently expressed in the microenvironment of TZ in comparison to the exocervix. 5,6,17 To the contrary, other groups have reported that the density of LC in the TZ is equal to that of the exocervix.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, we and others have suggested that other factors may contribute to the sensitivity of the TZ to SIL development. 6,17,18 For example, we have observed that the density of LC is significantly reduced and the immunosuppressive cytokine IL10 is more frequently expressed in the microenvironment of TZ in comparison to the exocervix. 5,6,17 To the contrary, other groups have reported that the density of LC in the TZ is equal to that of the exocervix.…”
mentioning
confidence: 97%
“…6,17,18 For example, we have observed that the density of LC is significantly reduced and the immunosuppressive cytokine IL10 is more frequently expressed in the microenvironment of TZ in comparison to the exocervix. 5,6,17 To the contrary, other groups have reported that the density of LC in the TZ is equal to that of the exocervix. 19,20 As an approach to understanding the factors involved in the initiation and progression of SILs, we sought to use a variety of methods to assess the differential density and the antigen presenting function of LC derived from TZ and SILs.…”
mentioning
confidence: 97%
“…Moreover, previous studies have reported a depletion and qualitative alterations of Langerhans cells in SIL compared to a normal squamous mucosa during the HPV-associated cervical carcinogenesis [1,45]. This ®nding might be due to an altered generation of DC or to a lack of maturation/migration of DC in relation to a decreased production of chemotactic factors by epithelial cells in the presence of HPV [14].…”
Section: Discussionmentioning
confidence: 91%
“…Several explanations have been proposed to explain the changes of Langerhans cells locally in SIL [16,21,29]. These lesions develop in the transformation zone of the cervix, where there is a low density of Langerhans cells, even in the absence of HPV infection [1,2,8]. Other authors have suggested that these changes might be due to the cytopathic e ect of the virus [38].…”
Section: Introductionmentioning
confidence: 99%
“…The squamous epithelium of the cervix is composed not only of keratinocytes (the primary target of HPV) but also of a type of immature dendritic cell (DC), the Langerhans cells (LC), which are important for the immunosurveillance of the squamous epithelium (Romani et al, 2003). Interestingly, the density of LC and their function are significantly reduced in the TZ compared to the ectocervix (Al- Saleh et al, 1995;Giannini et al, 2002), suggesting that keratinocyte/DC interactions could play a role in the establishment of SIL in this region. The production of cytokines/chemokines is necessary to maintain a balanced turnover of LC (Griffiths et al, 2005) and is most likely influenced by the complex differentiation state of keratinocytes, which is altered in metaplastic areas of the TZ and during cervical carcinogenesis (Hubert et al, 1999;Smedts et al, 1992).…”
Section: Role Of Sex Hormones On the Cervical Immune Microenvironmentmentioning
confidence: 99%